2008
DOI: 10.1253/circj.72.404
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coronary Artery Disease in Japanese Patients With Cerebral Infarction Impact of Metabolic Syndrome and Intracranial Large Artery Atherosclerosis

Abstract: Background Patients with cerebral infarction have a high prevalence of asymptomatic coronary artery disease (CAD) and other vascular diseases, but there is a lack of such data for Japanese patients, so the present study investigated the prevalence of cardiovascular disease (CVD) in Japanese patients and determined the predictors of CAD. Methods and ResultsThe study group comprised 104 patients with cerebral infarction who had no history of CVD. All patients underwent coronary computed tomographic angiography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…20,35 Prognostic Impact of MetS in Patients With CHF It has been reported that MetS is associated with a worse prognosis in patients with ischemic heart disease 12-17 and in those with stroke. 36 In the present study, MetS was associated with increased incidence of the composite endpoint of allcause death and atherosclerotic events. However, MetS had a significant prognostic impact on atherosclerotic events but not on all-cause death as an individual secondary endpoint.…”
Section: Study Limitationssupporting
confidence: 50%
“…20,35 Prognostic Impact of MetS in Patients With CHF It has been reported that MetS is associated with a worse prognosis in patients with ischemic heart disease 12-17 and in those with stroke. 36 In the present study, MetS was associated with increased incidence of the composite endpoint of allcause death and atherosclerotic events. However, MetS had a significant prognostic impact on atherosclerotic events but not on all-cause death as an individual secondary endpoint.…”
Section: Study Limitationssupporting
confidence: 50%
“…In 71 patients who were examined by 16-multislice coronary CT angiography, 25.4% had significant CAD [19]. The frequency was 37.5% in 104 patients who had a modified Rankin score <4 and were aged <80 years when they were examined by 8-multislice coronary CT angiography [30]. Recently, in 274 cases of nondisabling, noncardioembolic stroke or TIA in patients aged 45–75 years, CAD was detected in 18% using 64-multislice CT [20].…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to detect coronary plaques and to characterize plaque composition are also well-appreciated [5,6,7]. Several studies have investigated coronary characteristics of ischemic-stroke patients without known CAD [8,9,10]. However, these studies excluded embolic-stroke patients.…”
mentioning
confidence: 99%